Designing 2d Animation ”Duka Di Balik Harapan” About Renewal of the Legend of Telaga Warna for Teenagers as an Effort in Preserving West Javanese Culture - M Wahyu Riza; Sumarlin, Rully; Riky Taufik Afif (Universitas Telkom, 2025)
The Legend of Telaga Warna is one of the folk tales originating from the culture of West Java. However, this legend is notwidely known among teenagers in Bandung due to their lack of interest and the limited digital media presence of the story.Therefore, preservation efforts are needed to keep it relevant for future generations. One way to do this is through adaptingthe story into 2D animation. Existing adaptations have already existed, but mainly targeted children demographic, so there’sa need for a fresh adaptation that appeals to teenagers to trigger their interest in the legend of Telaga Warna. Hence, thewriter plans to design a 2D animation update of the Telaga Warna story as a means of preserving West Javanese culture.The designer will employ qualitative methods, collecting data through interviews with folklore experts, studying similaranimations, and reviewing literature. The aim is for this 2D animation design to captivate teenagers’ interest, encouragingthem to enjoy and learn about the legend of Telaga Warna, thus contributing to the preservation of West Javanese culture.